2013
DOI: 10.1007/s10841-013-9603-7
|View full text |Cite
|
Sign up to set email alerts
|

Within-patch mobility and flight morphology reflect resource use and dispersal potential in the dryad butterfly Minois dryas

Abstract: Knowledge of mobility is essential for understanding animal habitat use and dispersal potential, especially in the case of species occurring in fragmented habitats. We compared within-patch movement distances, turning angles, resting times, and flight-related morphological traits in the locally endangered butterfly, the dryad (Minois dryas), between its old populations occupying xerothermic grasslands and newly established ones in wet meadows. We expected that the latter group should be more mobile. Individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…The few studies existing revealed that protandrous structures being highly favorable under normal environmental conditions might become problematic for the survival of populations under highly unpredictable weather conditions (Junker et al ., ). Furthermore, flight activity necessary for males for the search for females and for females for the search for vacant habitat patches (Wiklund & Åhrberg, ; Baguette & Nève, ; Auckland et al ., ; Dover & Rowlingson, ; Nowicki & Vrabec, ; Slamova et al ., ; Zimmermann et al ., ; Kalarus et al ., ; Weyer & Schmitt, ) might considerably reduce their life expectance, thus representing a strong trade‐off in high mountain ecosystems (Junker et al ., ). However, some ecophysiological traits, at the first view, may appear contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies existing revealed that protandrous structures being highly favorable under normal environmental conditions might become problematic for the survival of populations under highly unpredictable weather conditions (Junker et al ., ). Furthermore, flight activity necessary for males for the search for females and for females for the search for vacant habitat patches (Wiklund & Åhrberg, ; Baguette & Nève, ; Auckland et al ., ; Dover & Rowlingson, ; Nowicki & Vrabec, ; Slamova et al ., ; Zimmermann et al ., ; Kalarus et al ., ; Weyer & Schmitt, ) might considerably reduce their life expectance, thus representing a strong trade‐off in high mountain ecosystems (Junker et al ., ). However, some ecophysiological traits, at the first view, may appear contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Our results may also reflect the fact that mobility, which is an accurate predictor of movements in seminatural settings (Ducatez et al ., ), may help find mates more rapidly, be detected more easily or can be used as a cue for sexual selection (Husak & Fox, ; Kalarus et al ., ). In a previous study, virgin females of Pararge aegeria were flying more often and therefore were detected by males more often (Bergman et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…As observed for both Boloria species as well as for other butterfly species (Zimmermann et al ., ; Zimmermann et al ., ; Slamova et al ., ; Kalarus et al ., ; Weyer & Schmitt, ), males were more flight‐active than females, which were mainly captured resting or feeding. These differences in flight activity might cause the sexual dimorphisms in nectar source selection observed in our study, driven by differential nutritional needs.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between the sexes in other behavioral patterns may however exist. For example, sometimes male and female individuals of one species differ in their dispersal behavior (Zimmermann et al, 2011;Kalarus et al, 2013;Weyer & Schmitt, 2013) or in their preferences for specific nectar sources (Rusterholz & Erhardt, 2000).…”
Section: Introductionmentioning
confidence: 99%